2018
DOI: 10.5539/jfr.v7n5p36
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Profile and Provitamin A Value of Sweet Potatoes Flours (Ipomoea batatas Lam) Consumed in Côte d’Ivoire

Abstract: Sweet potato is an important food security crop in Sub-Saharan Africa. In Côte d’Ivoire, the roots are widely consumed as supplementary staple food or secondary food. The present study is conducted to highlight the nutritive composition, antinutrients and β-carotene contents of local sweet potatoes consumed in Côte d’Ivoire. The nutritive properties and antinutritive factors of these sweet potatoes were investigated using standard methods. Results confirmed the energetic value (363±1.63-374.08±0.56 kcal/100 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
1
10
1
1
Order By: Relevance
“…This might be associated with variation in agroecology zones as well as genetic differences among studied accessions. The Zn content of anchote in this study is higher compared to sweet potato and yam Koua et al, 2018), but higher Zn content was reported in taro (Adane et al, 2013). Thus, it is safe to conclude that anchote would be a relatively good source of Zn, and its flour obtained from the raw tuber has preserved more Zn compared to the blanched and boiled.…”
Section: Zinc (Zn)contrasting
confidence: 58%
See 4 more Smart Citations
“…This might be associated with variation in agroecology zones as well as genetic differences among studied accessions. The Zn content of anchote in this study is higher compared to sweet potato and yam Koua et al, 2018), but higher Zn content was reported in taro (Adane et al, 2013). Thus, it is safe to conclude that anchote would be a relatively good source of Zn, and its flour obtained from the raw tuber has preserved more Zn compared to the blanched and boiled.…”
Section: Zinc (Zn)contrasting
confidence: 58%
“…According to the present study, the concentration of Mg in the raw, blanched, and boiled anchote flours dried at different temperatures ranged between 138.87 and 222.38 mg/100 g (Table 2) is relatively lower than sweet potato flour (49.37-540.87 mg/100 g) (Koua et al, 2018). On the other hand, it is by far higher than potato (21 mg/100 g) and taro (7.24 mg/100 g) (Adane et al, 2013;Rahman et al, 2015).…”
Section: Magnesium (Mg)mentioning
confidence: 55%
See 3 more Smart Citations